O-08 The impact of fear of failure on physician and nurse confidence and comfortableness in delivering end-of-life care. (19th November 2022) - Latham, John; Butchard, Sarah; Mason, Stephen
Abstract : Background: Only one systematic review has examined the emotions and psychological processes that clinicians experience, when providing end-of-life care to patients. The authors of this review highlighted how emotions of fear, and a sense of personal and professional failure may influence interactions between clinicians and patients. Very few empirical studies have measured the impact of psychological processes on the delivery of end-of-life care. Aims: To investigate whether fear of failure (FOF) influences physician and nurse confidence and comfortableness in delivering end-of-life care. Methods: We completed a cross-sectional questionnaire study across two large NHS hospital trusts in the UK, and national UK professional networks. We used three questionnaires for data collection: the Performance Failure Appraisal Inventory, the Self-Efficacy in Palliative Care scale and the Thanatophobia Scale. We used two-step multiple regression for data analysis. Results: We recruited 104 physicians and 101 specialist nurses from 20 hospital specialties. The study validated the use of the PFAI (FOF) measure and its subscales within a novel population group of medical professionals. We found that the more end-of-life conversations a clinician had positively impacted comfortableness and confidence with end-of-life care. 'Discomfort with death' was significantly associated with male gender clinicians, and physicians more than nurses. The FOF subscale 'Fearing loss of interest from important others' was shown to negatively impact a clinician's confidence in communicating. The FOF subscale 'Fear of devaluing one's self-estimate' was shown to negatively impact confidence in decision making, working with others, and a clinician's total self-efficacy. Conclusions: Our study suggests that psychological processes may influence a clinician's approach to end of life care, and highlights the need for clinicians to be aware of factors which may affect their performance. Drawing from wider psychological research, we make suggestions on how exploration of psychological strategies to reduce a clinician's fear of failure may positively help them to deliver end of life care more effectively.